MRI DTI and PDFF as Biomarkers for Lower Motor Neuron Degeneration in ALS - Lichtenstein, Thorsten; Sprenger, Alina; Weiss, Kilian; Große Hokamp, Nils; Maintz, David; Schlamann, Marc; Fink, Gereon R.; Lehmann, Helmar C.; Henning, Tobias D. (Frontiers in Neuroscience, 2021)
Objective: To evaluate the utility of nerve magnetic resonance imaging (MRI), diffusion tensor imaging (DTI), and muscle MRI multi-echo Dixon for assessing lower motor neuron (LMN) degeneration in amyotrophic lateral sclerosis (ALS). Methods: In this prospective observational cohort study, 14 patients with ALS and 13 healthy controls underwent a multiparametric MRI protocol, including DTI of the sciatic nerve and assessment of muscle proton density fat fraction of the biceps femoris and the quadriceps femoris muscles by a multi-echo Dixon sequence. Results: In ALS patients, mean fractional anisotropy values of the sciatic nerve were significantly lower than those of healthy controls. The quadriceps femoris, but not the biceps femoris muscle, showed significantly higher intramuscular fat fractions in ALS. Interpretation: Our study provides evidence that multiparametric MRI protocols might help estimate structural nerve damage and neurogenic muscle changes in ALS.